Blending performance of helical static mixer used for twin-pipe 3D concrete printing. (November 2022) - Tao, Yaxin; Rahul, A.V.; Mohan, Manu K.; Van Tittelboom, Kim; Yuan, Yong; De Schutter, Geert
Abstract: A twin-pipe pumping system has been developed to overcome the conflicting requirements in 3D concrete printing between pumping and deposition. In the twin-pipe pumping system, a helical static mixer, consisting of a series of mixing elements, is used to blend a cement-based mixture and a limestone-based mixture right before extrusion. As these two mixtures go through the static mixer, non-moving mixing elements continuously blend the materials in a flow-division pattern. However, the blending performance of the helical static mixer used for twin-pipe 3D concrete printing has not yet been reported. This paper presents the results of an experimental study on the relation between the mechanical behavior and the blending efficiency of the helical static mixer. Based on the binary images of the polished specimens printed with a different number of mixing elements, the blending performance was characterized by the coefficient of variation of the row-wise intensity distribution. A reasonable linear relationship was established between the mechanical strength (flexural strength and tensile strength) and the mixing homogeneity of the two mixtures. In addition, a higher number of mixing elements was observed to lead to a more dense pore structure, most probably due to the better compaction of the material by the higher pumping pressure.